The Ability of Several Biological Agents to Induce Resistance of Rice from Pyricularia oryzae Attacks In Vitro and In Vivo - Shyntiya Ayu Lestari; Evan Purnama Ramdan; Risnawati Risnawati; Edi Minjai Pribadi (Jurnal Proteksi Tanaman, 2022)
Rice (Oryza sativa Linnaeus) is the main food crop that is needed daily for the majority of Indonesian people. One of the diseases that increase rice production is the attack of pests and other diseases caused by Pyricularia oryzae. Biological agents are an alternative to control this disease. Therefore, the aim of this study was to determine the effectiveness of the induction of rice plant resistance using several biological agents against blast disease. The study was carried out in 2 stages, the first in vivo using a Randomized Block Design consisting of 4 biological agent treatments, namely Trichoderma sp., Bacillus subtilis, Pseudomonas fluorescens and sterile Aquades (control) which was repeated 6 times with each replication consisted of 3 plant samples so that the total number of samples observed was 72 plant samples. The second stage was carried out in vitro by inoculating P. oryzae on 3 pieces of rice plant leaves as a result of in vivo experiments. The design used was a completely randomized design with 4 agent treatments which were repeated 6 times. The results showed that the induction of rice plant resistance with P. fluorescens was able to reduce the severity of disease caused by P. oryzae attack (72.22%), with a decrease in efficacy of 25.48%, and the lowest AUDPC (691.66). In general, the resistance induction did not affect rice growth, but Trichoderma sp and P. fluorescens were able to increase the grain weight produced (3.11 and 2.80 g per plant, respectively).